The Two Intellectual Worlds of John Locke : Man, Person, and Spirits in the "Essay" - Yolton, John W. (Book collections on Project MUSE., 2004)
"Using his intimate knowledge of John Locke's writings, John W. Yolton shows that Locke comprehends "human understanding" as a subset of a larger understanding of other intelligent Beings-angels, spirits, and an omniscient God." "Yolton's book opens with an attempt to sort out several important terms basic to Locke's account of identity: man, self, person, and soul. A number of rarely examined components of Locke's thought emerge: the nature of man, the nature of a human being, and the place of man in the universe among the other creatures." "The Two Intellectual Worlds of John Locke also includes Yolton's exploration of Locke's commitment to immaterial principles for understanding the world; his obsession with happiness; the dialectical tensions between man, person, and soul; several interesting conjectures about spirits; and the notion of natural philosophy that includes speculation about spirits as well as bodies."--Jacket